Can breeder reproductive status, performance and egg quality be enhanced by supplementation and transition of n‐3 fatty acids?. Issue 4 (8th February 2016) - Delezie, E.; Koppenol, A.; Buyse, J.; Everaert, N.
Summary: The aim of this experiment was to investigate the effect of n‐3 fatty acid (FA) supplemented diets on breeder performance, productivity and egg quality. Breeders ( n = 480) were fed the supplemented diet from 18 weeks onwards; the inclusion level of n‐3 FA was increased from 1.5% to 3.0% from 34 weeks of age onwards until 48 weeks of age. Ross‐308 broiler breeders ( n = 480) were fed one of four different diets: a basal diet rich in n‐6 FA (control diet) or one of three diets rich in n‐3 FA. For the n‐3 FA diets, eicosapentaenoic acid (EPA, 20:5 n‐3) and docosahexaenoic acid (DHA, 22:6 n‐3) were fed to the broiler breeders at different ratios formulated to obtain EPA/DHA ratios of 1/1, 1/2 or 2/1. Differences in performance, reproduction and egg quality parameters due to n‐3 supplementation were noted more for the 1.5% followed by the 3.0% fed broilers than their 1.5% supplemented counterparts. Egg weight (p < 0.001) and egg mass (p = 0.003) were significantly lower and feed conversion (p = 0.008) significantly higher for the n‐3 FA (at 3.0% inclusion level) fed broilers compared to the control group. For the EPA‐ and DHA‐fed breeders, a higher proportional abdominal fat percentage (p = 0.025) and proportional albumen weight (%) (p = 0.041) were found respectively. Dietary treatments did not affect reproduction. It can be concluded that the results of the present experiment indicate no significant differences between treatments at 1.5% inclusion levels. However, increasing this level to 3.0% is not recommended due to the rather negative effects on the measured parameters. It should be further investigated whether these adverse effects were obtained due to (i) the higher supplementation level, (ii) combining a supplementation level of 1.5% with 3% or (iii) the duration of supplementation.